A review of the Odontura (Orthoptera, Phaneropterinae) from Italy, Malta, Algeria and Tunisia - Cassar, Louis F; Massa, Bruno (Zootaxa, 2022)
Taxa belonging to the genus Odontura have been studied since the former half of the 19th century. Species of the group are distributed across the western Mediterranean Basin and the central Mediterranean area, including the Iberian Peninsula and the Balearics, Sardinia, the countries of the Maghreb that border the Basin, Sicily and Malta. The present work examines a sizeable series of specimens of the genus Odontura, collected in Italy, Malta, Algeria and Tunisia, including type material of some of the species, and establishes synonymisations and a newly described species. Odontura borrei (described on a female from Constantine, Algeria) is synonymized with Odontura algerica (described on both sexes from Algeria), while Odontura arcuata (described on both sexes from west Sicily) is synonymized with Odontura stenoxypha (described on a female from Sicily), a sub-endemic to Sicily and Malta. Records of the latter from Sardinia belong to Odontura calaritana, while the female recorded from Majorca, previously identified as O. stenoxypha, remains unidentified. On the basis of a wide-ranging assessment of preserved specimens (from museums and private collections) and living material, this contribution describes a new species, Odontura martae sp. nov., from the island of Lampedusa (Italy) and Tunisia, and addresses patterns of geographical distribution in the context of biogeographical processes and associated dynamics.